Analysis of Capture Fisheries And Development Strategy in Berok River Nelatan Center, Central Bangka Regency - Nandika Alfan Firdaus; Kurniawan Kurniawan; Teguh Ferdinand (AQUASAINS, 2021)
Abstract This research aims to identify and analyze analyzing development strategies the fisheries catch at the Berok River Fishermen's Center, Central Bangka Regency. Data Primary in the form of questionnaires as many as 30 respondents by using method determination of the number of respondents saturated sample (sensus). Data analysis using descriptive methods by grouping fishing equipment into classification according to the Regulation of the Minister of Marine Affairs and Fisheries Republic of Indonesia Number 6 of 2010 concerning to Fishing Equipment. The results show that fishermen is the main livelihood in Berok River. There are 6 classifications and 4 types of main fishing equipment in the Berok River Fishermen's Center; millennium nets, stretch fishing rods, rawai fishing rods, pull trawls, boat charts, and plug charts. GPS, lights, solar panels as fishing aids. Ship material is banned from wood with the volume of the ship are <1 GT to 6 GT. The completeness of SIUP (Fishery Business Licence) and SIPI (Fishing Licence) of fishermen is 72%. Fishermen's recommendations on facilities and infrastructure include PPI (The base of Fish Landing), docks, fishing equipment procurement, and talud. The Strategy of Developing Fishermen's Center in Berok River is very feasible for PPI.Keywords Fishing Catch, Fishermen's Center, Berok River